The Influence of Halal Culinary in Increasing Economic Growth - Febrian Maulana Putra; Syamsul Hilal; Hanif; Muhammad Iqbal Fasa; Abdul Qodir Zaelani (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2023)
The research aims to determine a strategy for the development of halal cuisine with a focus on the culinarian center in the Lampung province to boost economic growth in the Province of Lampung. The investigation uses qualitative descriptive methods of research using data collection techniques consisting of field surveys, in-depth interviews, and 7P analysis of products, prices, places, promotions, people, processes, and physical evidence related to the development of halal cuisine in the region. The results of the research show that great potential lies in the development of halal cuisine in the Province of Lampung with strategies that include quality improvement, effective marketing, and collaboration with halal certification bodies that have the potential to enhance the potential of Muslim tourists. By maximizing the halal culinary potential, the Province of Lampung can strengthen its contribution to economic growth and enhance the competitiveness of the regional tourism and gastronomic industries. The problem with culinary halal is that there are still culinaries that do not have a halal certificate, This is due to the minimum of information, which is necessary to do more socialization by the Organizing Authority for the Guarantee of Halal Products (BPJH) so that culinarian perpetrators who have not known can know the importance of halal certificates.